Donum Studi di storia della pittura, della scultura e del collezionismo a Firenze dal Cinquecento al Settecento - Betti, Marco; Brovadan, Carlotta Paola (Studi e saggi, 2020)
The essays collected in Donum discuss different aspects of Florentine art from the 16th to the 18th century, such as sculptures displayed in gardens and palaces, the collecting preferences and strategies of the Medici family and those of the Tuscan aristocracy, drawings and paintings by local and foreign artists, and baroque wall decoration: these topics are analyzed in light of newly discovered artworks or previously unpublished documents. The common thread binding the papers together is the research method based on the study of archival sources and historical contexts, and on the connoisseurship. The volume gathers art historians who had been involved in the conference held in 2016 in honor of Mara Visonà as well as other scholars educated at the University of Florence.